Nutritional supplements as a source for positive doping cases? - Kamber, M.; Baume, N.; Saugy, M.; Rivier, L. (International Journal of Sport Nutrition and Exercise Metabolism, 2001)
We report the findings of the analysis of 75 different nutritional supplements bought through the internet. Seven products (all from the class of prohormones) contained other hormone substances than indicated on the labels, and two further products contained ephedrine and caffeine without a clear indication on the labels.